Penerapan Asas Equality Before The Law dalam Penanganan Kasus Narkotika Oleh LBH Legundi Surabaya (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This research analyzes the application of the equality before the law principle in handling narcotics cases by the Legal Aid Institute (LBH) Legundi Surabaya. The principle of equality before the law is a fundamental principle guaranteed in Article 27 paragraph (1) of the 1945 Constitution, yet its implementation in narcotics law enforcement still faces various challenges. This study employs a normative juridical method with a qualitative approach to examine LBH Legundi's strategies in ensuring clients fully obtain their constitutional rights. The findings reveal that although LBH Legundi has implemented various strategies such as detailed examination of arrest procedures, optimization of legal instruments, and efforts for detention suspension, the application of the equality before the law principle remains hindered by several factors. The main challenges include strong social stigma against narcotics offenders, limited resources of legal aid institutions, disparities in judicial decisions, structural barriers in accessing justice, weak supervision systems, minimal systemic support from the state, and a law enforcement mindset that remains punitive rather than rehabilitative. This condition creates a significant gap between suspects from economically disadvantaged backgrounds and those from affluent backgrounds, which contradicts the spirit of substantive justice. The study concludes that realizing the principle of equality before the law requires comprehensive reform touching structural, cultural, and systemic aspects of Indonesia's criminal justice system.